Microbiota is structured by gut regions, life stage, and diet in the Black Soldier Fly (Hermetia illucens) - Auger, Laurence; Deschamps, Marie-Hélène; Vandenberg, Grant; Derome, Nicolas (Frontiers in Microbiology, 2023)
The larvae of the Black Soldier Fly (Hermetia illucens) provide numerous ecological benefits, leading to significant commercial advancements. These benefits include the bioconversion of low-value waste into high-value feed and soil amendments. Understanding how the bacterial and eukaryotic microbiota communities affect host performance becomes vital for the optimization and specialization of industrial-scale rearing. This study investigates H. illucens-associated microbiota taxonomic composition and dynamics across the developmental cycle (eggs, neonates, larvae, prepupae, and imago X0 to second generation X1) when reared on two substrates: (i) plant-based (Housefly Gainesville diet) and (ii) animal-based (poultry hatchery waste). By using the 16S gene amplicon metataxonomic approach, we found that the results revealed that bacterial microbiota inherited from parents reared on a different substrate may have induced dysbiosis in the progeny. Specifically, the interaction networks of individuals reared on hatchery waste showed a high prevalence of negative interactions and low connectivity. Proteobacteria (39–92%), Firmicutes (4–39%), Bacteroidota (1–38%), and Actinobacteria (1–33%). In animal feed-reared individuals, Firmicutes reached the highest relative abundance (10–80%), followed by Proteobacteria (6–55%), Actinobacteria (1–31%), and Bacteroidota (0–22%). The rearing substrate was the main driver of microbiota composition, while the developmental stage influenced only the whole individual's bacterial microbiota composition. Gut regions were associated with distinct bacterial composition and richness, with diversity decreasing along the digestive tract. For the first time, microeukaryotes of the microbiota other than Fungi were investigated using 18S genetic marker amplicon sequencing with novel blocking primers specific to the Black Soldier Fly. Microeukaryotes are a neglected part of multitrophic microbiota communities that can have similar effects on their hosts as bacterial microbiota. Microeukaryotes from seven orders were identified in black soldier flies, including potential pathogens (e.g., Aplicomplexa group). Nucletmycea were the dominant class throughout development, followed by Holozoa and Stramenophiles. The eukaryote microbiota was structured by developmental stages but not by gut regions. Insights from this study are a stepping stone toward the microbiological optimization of black soldier flies for industrial rearing, highlighting how a synthetic microbiota assembly should be tailored to the rearing environment of the larvae at a targeted developmental stage.